Islamic Art and Creative Expression: A Conceptual Analysis of Aesthetic and Religious Values - Selfa Afia; Ulfah Alfiyyah (Borneo International Journal of Islamic Studies, 2026)
Contemporary discussions on Islamic art often raise questions regarding the relationship between artistic freedom and religious commitment. This study examines how art is conceptualized within Islamic thought and explores the extent to which creative expression may coexist with religious values. Employing a qualitative literature review with an interpretive content analysis approach, this study draws upon primary Islamic sources, including the Qur’an and hadith, as well as classical and contemporary Islamic scholarship and academic literature on Islamic aesthetics. The analysis focuses on three dimensions: theological foundations of art, ethical boundaries of artistic expression, and the socio-spiritual functions of art in Islamic traditions. The findings indicate that Islamic perspectives do not reject artistic creativity; rather, art is understood as a meaningful cultural and spiritual practice guided by the principles of tawhid, morality, and social responsibility. The study argues that Islamic art represents a dynamic space in which aesthetic innovation and religious values are continuously negotiated. This research contributes to broader discussions in Islamic Studies by offering a conceptual framework for understanding the interaction between creativity, spirituality, and religious ethics in contemporary Islamic contexts.